2018
DOI: 10.1017/s1355617718000097
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction by Disclosure? Stereotype Threat as a Source of Secondary Neurocognitive Malperformance in Obsessive-Compulsive Disorder

Abstract: Stereotype threat negatively impacted neuropsychological performance on an attention task. The threat cue was perhaps too weak or the stereotype threat was already internalized by the patients and "saturated" at baseline so that no effect emerged on the other measures. Implications for clinical trials are discussed. (JINS, 2018, 24, 584-592).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Second, other contextual factors or mediators need to be examined for their role in functioning. For example, it was recently found that stereotype threat may also lead to secondary impairment [48]. In AUD, motor impairment (e.g., ataxia) may also play a role in timed tests with a strong motor component (e.g., the TMTs).…”
Section: Discussionmentioning
confidence: 99%
“…Second, other contextual factors or mediators need to be examined for their role in functioning. For example, it was recently found that stereotype threat may also lead to secondary impairment [48]. In AUD, motor impairment (e.g., ataxia) may also play a role in timed tests with a strong motor component (e.g., the TMTs).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also suggested that OCD patients may perform worse due stereotype threat. This suggests that internalized negative beliefs about performing worse due to their disorder may actually lead to worse task performance by itself (Moritz, Spirandelli, Happach, Lion, & Berna, 2018). Neuroimaging studies provide some support for the "executive overload model", as worse task performance has been related to more state distress and amygdala activation during planning in both OCD, panic disorder, and hypochondriasis (O.…”
Section: Emotions Cognition and Their Interactionmentioning
confidence: 99%
“…Future harmonization studies aiming to elucidate these sources of noise should be conducted to establish the role of motivation, attention, stigma, and evaluators' expertise in the data, among other factors related to the subjects' understanding of the instructions. Particularly, the stereotype threat has been indicated to alter neurocognitive performance (Moritz et al, 2018), and it also should be taken into account during the evaluation, especially in clinical trials and comparing psychiatric populations with healthy participants.…”
Section: Discussionmentioning
confidence: 99%